2010
DOI: 10.1086/649021
|View full text |Cite
|
Sign up to set email alerts
|

Imipenem Resistance in Pseudomonas aeruginosa Emergence, Epidemiology, and Impact on Clinical and Economic Outcomes

Abstract: The prevalence of IRPA infection or colonization has increased significantly, with important implications for both clinical and economic outcomes. Interventions to curb this continued increase and strategies to optimize therapy are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
80
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 29 publications
10
80
0
1
Order By: Relevance
“…The drug resistance rates are largely determined by the pattern of antibiotic usage in the hospital setting. Ciprofloxacin use has been reported to be an independent risk factor for development of fluoroquinolone and carbapenem resistance [12][13][14]. Therefore, several interventions aimed at modifying the antibiotic prescription pattern have been tried, to decrease the resistance rates.…”
Section: Discussionmentioning
confidence: 99%
“…The drug resistance rates are largely determined by the pattern of antibiotic usage in the hospital setting. Ciprofloxacin use has been reported to be an independent risk factor for development of fluoroquinolone and carbapenem resistance [12][13][14]. Therefore, several interventions aimed at modifying the antibiotic prescription pattern have been tried, to decrease the resistance rates.…”
Section: Discussionmentioning
confidence: 99%
“…Data from U.S. ICU studies, surveillance studies, the National Nosocomial Surveillance System, and the SENTRY Antimicrobial Surveillance Program have shown that overall susceptibilities within a 10-year period have declined significantly for all drug classes studied, and these trends are likely mirrored in individual institution antibiograms as well (82,135,182). Nationally, for example, multidrug resistance of P. aeruginosa to three or more antipseudomonal agents rose from 4% in 1993 to 14% in 2002 (P Ͻ 0.001), and it continues to rise (148,187).…”
Section: Arguments In Favor Of Combination Therapy Broad Spectrum Of mentioning
confidence: 99%
“…To assess risk factor variables, we used a comprehensive clinical and administrative University of Pennsylvania health system database, which contains data for all hospitalizations since January 1, 2001, and has been used successfully for similar studies of antimicrobial drug resistance (19)(20)(21). Data elements obtained were age, sex, race, hospital (HUP or PPMC), admission as a transfer from another facility (i.e., outside hospital, longterm care facility, rehabilitation center), location within the hospital at the time of culture (i.e., intensive care unit or not intensive care unit), length of hospital stay before culture, prior admission to HUP or PPMC within the past 30 days, Charlson index (22), and all-patient refi ned-diagnosisrelated group (APR-DRG) classifi cation.…”
Section: Variablesmentioning
confidence: 99%